2002
DOI: 10.1021/ja012152f
|View full text |Cite
|
Sign up to set email alerts
|

Development of the [3 + 2] Annulations of Cyclohexenylsilanes and Chlorosulfonyl Isocyanate:  Application to the Total Synthesis of (±)-Peduncularine

Abstract: The synthesis of (+/-)-peduncularine was accomplished using the [3 + 2] annulation of an allylic silane with chlorosulfonyl isocyanate to assemble the bicyclic core of the alkaloid. The stereochemistry of the annulation product was employed to control the installation of the indolylmethyl side chain at C-7 with complete stereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 45 publications
0
59
0
1
Order By: Relevance
“…The reduction of C 8 H 7 NCO under vacuum conditions in hexamethylphosphoramide (HMPA) at 293 K with sodium metal, 31 or in THF (with 1 equiv of 18-crown-6) with potassium metal at 180 K, gives rise to an EPR spectrum that upon computer simulation reveals that the anion radical of a substituted [8]annulene had been generated, Figure 1. 32,33 The two larger a H 's (4.13 G (2 Hs) and 4.37 G (2 Hs)) come from coupling to the four hydrogens on the even numbered carbons, while the smaller a H (2.295 G (3 Hs)) is from the hydrogens on the odd numbered carbons.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reduction of C 8 H 7 NCO under vacuum conditions in hexamethylphosphoramide (HMPA) at 293 K with sodium metal, 31 or in THF (with 1 equiv of 18-crown-6) with potassium metal at 180 K, gives rise to an EPR spectrum that upon computer simulation reveals that the anion radical of a substituted [8]annulene had been generated, Figure 1. 32,33 The two larger a H 's (4.13 G (2 Hs) and 4.37 G (2 Hs)) come from coupling to the four hydrogens on the even numbered carbons, while the smaller a H (2.295 G (3 Hs)) is from the hydrogens on the odd numbered carbons.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…33b, 34 On the basis of the EPR results obtained, our initial conclusion was that we had successfully generated the anion radical of C 8 H 7 NCO in solution for two important reasons: (1) The unpaired electron clearly resides within the annulene ring and exhibits coupling to only one nitrogen atom (a N = 0.58 G) and (2) in previous studies with PhNCO •− , we found that the NCO Scheme 1. Synthesis of [8]Annulenyl Isocyanate (1) Starting from Cyclooctatetraene (COT) Figure 1. (Upper) X-band EPR spectrum recorded at 180 K after a THF solution containing [8]annulenyl isocyanate (C 8 H 7 NCO) with 1 equiv of 18-crown-6 was exposed to K metal under vacuum.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations